Physical therapy intervention for low back pain et causa lumbar spondylolisthesis: a clinical case report - Wardojo, Sri Sunaringsih I.; Rosadi, Rakhmad; Uddani, Musdalifa T. (International Journal of Research in Medical Sciences, 2022)
Lumbar spondylolisthesis is a kind of low back pain (LBP) that involves the displacement of one of the vertebral bodies as a result of trauma. Spondylolisthesis can lead to spondylolysis or fracture injury, which commonly occurs in the elderly as a result of degenerative disorders. However, physical therapy modalities such as transcutaneous electrical nerve stimulation (TENS), infrared (IR), and exercise treatment in the form of William flexion exercise can be employed in situations of LBP that cause lumbar spondylolisthesis. Thus, this clinical case study aimed at investigate the effects of these physical therapy intervention towards patients with LBP spondylolisthesis. LBP was reported by a 62-year-old female patient in Malang clinic. Patient had difficulties walking and sitting for lengthy periods of time. Straight leg raise (SLR) examination, Valsalva test, Trendelenberg test and Barthel index were performed as the physical examination test. While, during intervention period, patient was given TENS, IR, and William flexion exercise for twice a week, with each movement being repeated ten times during three months intervention. There was a positive change in the form of a decrease in tenderness, which was followed by a decrease in active lumbar motion discomfort and a decrease in spasm. Tenderness and motion discomfort are both symptoms of pain alterations. The findings of the treatment show that traditional treatments such as TENS and IR, as well as exercises using the William's flexion exercises approach, can help the elderly with LBP related to spondylolisthesis reduce pain and increase muscular tone.